Pollutant removal method
Patent Information
- Application Number
- JP2023128973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2043-08-08
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for removing contaminants using a self-peeling film that is applied to a target surface and then peels off spontaneously as the coating film dries. [Background technology]
[0002] In general, methods for removing dirt and dust particles such as fine particles adhering to or remaining on the surface of equipment include washing with water or solvents, wiping, scraping off with mechanical force, and suction. However, in these operations, there is a risk that workers may inhale the cleaning liquid or scattered dust. In particular, when the cleaning liquid used is a substance harmful to the human body or the substance to be removed is a contaminated substance containing asbestos, harmful chemicals, radioactive substances, etc., measures are required to prevent workers from inhaling the cleaning liquid or contaminated substances. For example, since contaminated substances at nuclear power plants contain radioactive substances, workers during cleaning and decommissioning work are at risk of exposure due to inhalation or adhesion. Therefore, there is a demand for technology to remove such contaminated substances efficiently and safely.
[0003] Contaminants tend to remain on the surface of equipment, especially in the fine details such as uneven areas. One effective technique for removing such contaminants without scattering them is to use a peelable coating, which involves applying paint to the target surface, drying, and then peeling off the coating to remove the adsorbed contaminants. Although this technique is effective for removing contaminants remaining in the fine details, it is difficult to create a peeling start point at the edge of the coating when peeling off after drying, and if this takes a long time, the risk of workers inhaling or being exposed to harmful substances increases. Another problem is that it is difficult to collect the peeled off coating in an environment where people cannot enter.
[0004] As a means to address these issues, if a self-peeling coating could be developed that peels off spontaneously after drying, collection would be simple and quick, and remote work using robots or other devices would also be possible.
[0005] As a technology related to self-peeling films, Patent Document 1 discloses a developer removal material for penetrant inspection with self-peeling properties, which is made by dissolving a cellulose-based synthetic resin capable of forming a peelable resin film in a volatile organic solvent. Patent Document 2 discloses a means for peeling off a film made mainly of an aqueous paint and containing a water-soluble thickener by swelling it with water. Meanwhile, Patent Document 3 discloses a method, which is different from the self-peeling film technology, in which a coating composition is applied to a substrate in advance to form a barrier coating, and after contaminants are deposited on the barrier coating, the barrier coating and contaminants are removed from the substrate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 59-171841 [Patent Document 2] JP 2000-327958 A [Patent Document 3] Special Publication No. 2010-530806 Summary of the Invention [Problem to be solved by the invention]
[0007] The technology described in Patent Document 1 has problems such as an unpleasant odor due to the inclusion of a considerable amount of organic solvent and insufficient self-peeling properties. The method described in Patent Document 2 requires the addition of water to the coating to cause it to swell. The method described in Patent Document 3 involves removing the barrier coating and contaminants by washing or wiping, etc., and the method for removing the coating is not simple.
[0008] Therefore, the present invention relates to a method for removing pollutants, which uses a composition for forming a self-peeling film, which is applied to a target surface and then dried to spontaneously peel off the coating film, thereby enabling the removal of pollutants and the peeling and recovery of the coating film that has adsorbed the pollutants to be carried out easily and in a short time. [Means for solving the problem]
[0009] The present inventors have discovered that by incorporating a polymer containing vinyl alcohol as a constituent unit and polystyrene sulfonic acid or a salt thereof in a specific ratio in a volatile solvent, it is possible to remove contaminants while solving the above-mentioned requirements, and have completed the present invention.
[0010] The present invention provides a method for removing contaminants from a target surface, comprising the steps of: A process of applying a self-peeling film-forming composition containing the following components (A) to (C), in which the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less, to a target surface having contaminants attached thereto to form a coating film; drying the coating; removing contaminants together with the coating film by self-peeling of the coating film accompanying the drying; The present invention provides a method for removing pollutants, comprising: (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
[0011] The present invention further provides use of a composition for forming a self-peeling film, which contains the following components (A) to (C), and in which the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less, for removing contaminants from a target surface by self-peeling as the coating film dries. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
[0012] The present invention further provides a composition for forming a self-peeling film, comprising the following components (A) to (C), in which the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents Effect of the Invention
[0013] The contaminant removal method of the present invention utilizes a composition for forming a self-peeling film that is applied to a target surface and then peels off from the periphery of the coating film as the coating film dries, allowing the removal of contaminants and the peeling and recovery of the coating film that has adsorbed the contaminants to be carried out easily and in a short time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In the present invention, "self-peeling" refers to the fact that after the composition for forming a self-peeling film is applied to a target surface, the volatile solvent evaporates, and the coating film gradually peels off from the periphery due to the internal stress of the coating film components without the application of a peeling force. More specifically, the peeling degree of the dried coating film measured by the following evaluation method is preferably 20% or more and 100% or less. This peeling degree is preferably 30% or more and 100% or less, more preferably 40% or more and 100% or less, even more preferably 50% or more and 100% or less, even more preferably 60% or more and 100% or less, and even more preferably 70% or more and 100% or less. <Evaluation method> The composition was applied at 0.3 g / cm to an epoxy resin-coated substrate. 2 The adhesive area S1 of the composition that has spread wet on the substrate before drying and the area S2 of the coating film that is in contact with the substrate after drying are measured, and the calculated value (S1-S2) / S1 is the degree of peeling.
[0015] Examples of polymers containing vinyl alcohol as a constituent unit of component (A) include polyvinyl alcohol, as well as anion-modified or cation-modified modified polyvinyl alcohol, vinyl acetate-ethylene copolymers and hydrolysates thereof, etc. Among these, polyvinyl alcohol and hydrolysates of vinyl acetate-ethylene copolymers are preferred in that they form an appropriate coating film through the interaction of intermolecular hydrogen bonds with component (B) and further develop the self-peeling properties of the dried coating film.
[0016] The glass transition point of the polymer of component (A) is preferably 0° C. or higher, more preferably 10° C. or higher, even more preferably 20° C. or higher, and even more preferably 30° C. or higher, from the viewpoint of exhibiting self-peeling properties due to internal stress during drying. From the viewpoint of improving film strength, the glass transition point is preferably 120° C. or lower, more preferably 110° C. or lower, even more preferably 100° C. or lower, and even more preferably 90° C. or lower. If the glass transition point is lower than 0° C., the self-peeling properties will not be exhibited.
[0017] Furthermore, from the viewpoint of improving the formation of a coating film and the self-peeling property of a dried coating film, the weight average molecular weight of component (A) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, and even more preferably 40,000 or more. Also, from the viewpoint of improving the coatability, it is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, and even more preferably 200,000 or less.
[0018] Commercially available polyvinyl alcohol products that can be used include Kuraray Poval 3-98, 5-98, 28-98, 60-98, 27-95, 27-96, 17-94, 7-92, 3-88, 5-88, 22-88, 44-88, 95-88, and 48-80 (manufactured by Kuraray Co., Ltd.). Furthermore, commercially available products of the hydrolysate of vinyl acetate-ethylene copolymer include Exeval RS-2117 and RS-1717 (manufactured by Kuraray Co., Ltd.).
[0019] The content of component (A) in the composition for forming a self-peeling film of the present invention is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and even more preferably 1.5% by mass or more from the viewpoint of fully expressing the self-peeling property of the dried coating film, and from the viewpoint of improving the coating property, it is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, even more preferably 7% by mass or less, and even more preferably 5% by mass or less. The content of component (A) in the composition for forming a self-peeling film can also be preferably 1.5 to 20% by mass, more preferably 1.5 to 15% by mass, even more preferably 1.5 to 10% by mass, even more preferably 1.5 to 7% by mass, and even more preferably 1.5 to 5% by mass.
[0020] The sulfonation rate of the polystyrene sulfonic acid or a salt thereof of component (B) is 89% or more, but from the viewpoint of fully exhibiting self-peeling properties when used in combination with component A, the sulfonation rate is preferably 95% or more, more preferably 98% or more, and even more preferably 99% or more.
[0021] It is known from the literature that the higher the sulfonation rate of polystyrene sulfonic acid or its salts, the higher the glass transition point (BALDING, Paul, et al. Physical Properties of Sodium Poly (styrene sulfonate): Comparison to Incompletely Sulfonated Polystyrene. Macromolecules, 2022, 55.5: 1747-1762). For example, it is said that the Tg at a sulfonation rate of 89% is about 210°C, and at a sulfonation rate of close to 100%, the Tg exceeds the decomposition temperature (440°C). The glass transition point of component (B) is preferably 210°C or higher, more preferably 300°C or higher, even more preferably 400°C or higher, and even more preferably 440°C or higher, in order to fully exhibit self-peeling properties due to internal stress during drying.
[0022] The weight average molecular weight of component (B) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and even more preferably 100,000 or more, from the viewpoint of improving coating film formation and self-peeling of the dried coating film, and is preferably 10,000,000 or less, more preferably 5,000,000 or less, and even more preferably 2,000,000 or less, from the viewpoint of improving coatability.
[0023] As commercially available products of polystyrene sulfonic acid or a salt thereof, PS-100 (manufactured by Tosoh Finechem Corporation), PS-50 (same manufacturer), PS-5 (same manufacturer), etc. can be used.
[0024] The content of component (B) in the composition for forming a self-peeling film of the present invention is preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 8% by mass or more, and even more preferably 10% by mass or more from the viewpoint of fully expressing the self-peeling property of the dried coating film, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less from the viewpoint of improving the coatability. That is, the content of component (B) in the composition for forming a self-peeling film is preferably 5 to 50% by mass, more preferably 7 to 40% by mass, even more preferably 8 to 30% by mass, and even more preferably 10 to 25% by mass.
[0025] The mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more, preferably 0.65 or more, more preferably 0.70 or more, even more preferably 0.75 or more, even more preferably 0.80 or more, and 0.95 or less, preferably 0.94 or less, more preferably 0.93 or less, from the viewpoint of fully expressing the self-peeling property of the dried coating film and from the viewpoint of the strength of the dried coating film. The mass ratio (B) / [(A)+(B)] can also be preferably 0.70 to 0.94, more preferably 0.75 to 0.94, even more preferably 0.75 to 0.93, and even more preferably 0.80 to 0.93.
[0026] The volatile solvent of component (C) is a substance that is volatile in a liquid state, and is selected from water and a volatile organic solvent, and preferably contains water, and more preferably contains water as a main component. In addition, from the viewpoint of drying after application to form a suitable dried coating film, a volatile organic solvent can be used in combination with water. Examples of the volatile organic solvent include alcohols such as ethanol, methanol, and propanol, ketones such as acetone, and tetrahydrofuran, and one or more selected from alcohols and ketones are preferred. In addition, the volatile organic solvent preferably has a vapor pressure of 0.01 kPa to 106.66 kPa at 20°C, more preferably 0.13 kPa to 66.66 kPa, even more preferably 0.67 kPa to 40.00 kPa, and even more preferably 1.33 kPa to 40.00 kPa. When component (C) contains a volatile organic solvent, the proportion of the volatile organic solvent is preferably 50 mass% or less, further 20 mass% or less, and further 10 mass% or less of the entire component (C).
[0027] The content of component (C) in the composition for forming a self-peeling film of the present invention is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, from the viewpoint of improving the coatability to the target surface, and is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less, from the viewpoint of improving the self-peeling property.
[0028] The self-peeling film forming composition of the present invention may further contain potassium iodide as component (D). When the contaminant is a substance that reacts with iodine, such as radioactive substances such as cesium-134, cesium-137, strontium-90, cobalt-60, etc., the coating film will become colored, which is a sign of purification, and the removal effect can be confirmed by repeating the coating and peeling process until the color disappears.
[0029] The content of component (D) in the composition for forming a self-peeling film of the present invention is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 3 mass% or more from the viewpoint of expressing coloration derived from iodide, and is preferably 15 mass% or less, more preferably 12 mass% or less, and even more preferably 10 mass% or less from the viewpoint of incorporation into the composition for forming a self-peeling film.
[0030] [Optional ingredients] The self-peeling film-forming composition of the present invention may further contain components such as surfactants, thickeners, plasticizers, preservatives, etc., within the range that does not impair the self-peeling properties of the dried coating film.
[0031] The surfactant may be any of an anionic surfactant, a cationic surfactant, a nonionic surfactant, and an amphoteric surfactant.
[0032] The thickener may be a component other than the component (A) of the present invention, such as an organic thickener such as xanthan gum, gellan gum, locust bean gum, or guar gum, or an inorganic thickener such as bentonite, magnesium aluminum silicate, laponite, hectorite, or silicic anhydride, at a low concentration such that a film is not formed by itself. Examples of the plasticizer include propylene glycol, 1,3-butylene glycol, glycerin, isopentylene glycol, hexylene glycol, dipropylene glycol, polyethylene glycol, and polypropylene glycol. Examples of the preservative include phenoxyethanol, benzoic acid, benzisothiazoline, sorbic acid, and propionic acid.
[0033] [Method of removing pollutants] The method for removing contaminants of the present invention includes the steps of applying a composition for forming a self-peeling film, which contains components (A) to (C) and has a mass ratio (B) / [(A)+(B)] of component (B) to component (A) of 0.6 or more and 0.95 or less, to a target surface having contaminants attached thereto to form a coating film, drying the coating film, and removing the contaminants together with the coating film by the self-peeling of the coating film resulting from the drying.
[0034] In the present invention, the self-peeling film forming composition of the present invention is applied to a target surface on which contaminants are attached, so that the attachments on the target surface are adsorbed to the composition, and in the process of drying the composition, the contaminants are adsorbed to the dried coating. As a result, the dried coating to which the contaminants are adsorbed spontaneously peels off from the target surface as it dries. At this time, the coating of the self-peeling film forming composition of the present invention gradually peels off from the periphery of the coating as it dries. Thereafter, the contaminants on the target surface can be removed by collecting the peeled dry coating.
[0035] Target surfaces for removing contaminants include surfaces of synthetic resins (epoxy resins, polyvinyl chloride, acrylic resins, polyethylene, etc.), painted surfaces of synthetic resins, metal surfaces, glass surfaces, ceramic surfaces, concrete surfaces, mortar surfaces, surfaces of cement solidified bodies, and asphalt surfaces, and the surfaces may be smooth or have fine irregularities. Fine irregularities can be applied to a range that does not inhibit self-peeling of cement surfaces, etc. The target surfaces may be installed on floors, walls, ceilings, or other inclined places such as slopes of various facilities such as power plants, factories, warehouses, office buildings, apartment buildings, parking lots, roads, bridges, and tunnels. The contaminants to be removed can also include powdery or granular deposits (for example, dust such as asbestos, dust, sand, sludge, slime, and soot), oily deposits (for example, oily stains such as crude oil and tar, paints such as oil-based pens and lacquer sprays), deposits of plant and animal origin (moss, algae, bird droppings, dead insects, etc.), salt, etc. The technology of the present invention can be used to remove contaminants from nuclear power plants, as well as asbestos and other harmful substances, and for work in harsh environments.
[0036] For application to the target surface, a spatula, a dragonfly, a rake, a brush, a roller, a sprayer, a sprayer, etc. can be used. In addition to directly spreading the composition using the above-mentioned tools, application by spraying, etc. is also included. The amount of the self-peeling film-forming composition of the present invention applied to the target surface is preferably 0.1 kg / m from the viewpoint of enhancing the self-peeling property of the dried coating film. 2More preferably, 0.5 kg / m 2 More preferably, 1 kg / m 2 From the viewpoint of ease of curing and film formation, it is preferably 10 kg / m 2 Less than or equal to 8 kg / m 2 Less than 5 kg / m, more preferably 2 More preferably, 3 kg / m or less 2 The following is the result.
[0037] The drying step of the coating film after applying the composition to the target surface may be natural drying or air drying, or may utilize a heat source such as a halogen heater. The environmental temperature in the drying step is preferably -10°C or higher, more preferably 0°C or higher, and even more preferably 5°C or higher, and is preferably 60°C or lower, more preferably 55°C or lower, and even more preferably 50°C or lower.
[0038] In the contaminant removal method of the present invention, from the viewpoint of avoiding inhibition of self-peeling, it is preferable that the process before the start of self-peeling does not include a process of applying or coating water or an aqueous composition containing 50 mass % or more of water other than the composition for forming a self-peeling film of the present invention.Furthermore, it is more preferable to carry out a process of drying the coating film without any other process following the process of applying the composition for forming a self-peeling film of the present invention.
[0039] After the self-peeling film-forming composition of the present invention is applied to a target surface, the coating film begins to shrink as the volatile solvent (water) of component (C) evaporates, but while the coating film is in a high water content state, the molecular chains of the film-forming component of component (A) can move freely and no internal stress is generated. As the coating film dries and reaches a low water content state, the coating film shrinks further and the thermal motion of the molecular chains of component (A) is frozen. This generates strong internal stress, which causes the coating film to exhibit a peeling force greater than the adhesive force with the target surface, making it easier to peel off spontaneously from the edge.
[0040] With respect to the above-described embodiment, preferred aspects of the present invention will be further disclosed below.
[0041] <1> 1. A method for removing contaminants from a target surface, comprising: A process of applying a self-peeling film-forming composition containing the following components (A) to (C), in which the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less, to a target surface having contaminants attached thereto to form a coating film; drying the coating; removing contaminants together with the coating film by self-peeling of the coating film accompanying the drying; A method for removing contaminants comprising: (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
[0042] <2> Use of a composition for forming a self-peeling film, which contains the following components (A) to (C), and in which the mass ratio of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less, (B) / [(A)+(B)], for removing contaminants from a target surface by self-peeling as the coating film dries. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
[0043] <3> The application of the self-releasing film forming composition to the target surface is preferably carried out using a dragonfly, a rake, a brush, a roller or a spray; <1> or <2> 2. The method or use for removing pollutants as described above.
[0044] <4> The amount of the self-releasing composition applied to the target surface is preferably 0.1 kg / m 2 More preferably, 0.5 kg / m 2 More preferably, 1 kg / m 2 More preferably, it is 10 kg / m 2 Less than or equal to 8 kg / m2 Less than 5 kg / m, more preferably 2 More preferably, 3 kg / m or less 2 Below is the <1> ~ <3> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0045] <5> Preferably, after the step of applying the composition for forming a self-peeling film to a target surface to form a coating film, a step of drying the coating film is performed without any other steps. <1> ~ <4> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0046] <6> The drying step is preferably carried out in an environment of -10°C or higher, more preferably 0°C or higher, and even more preferably 5°C or higher, and preferably 60°C or lower, more preferably 55°C or lower, and even more preferably 50°C or lower. <1> ~ <5> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0047] <7> The coating film of the self-releasing composition preferably peels off from the peripheral portion as it dries. <1> ~ <6> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0048] <8> Component (A) is polyvinyl alcohol, anionically modified polyvinyl alcohol, cationically modified polyvinyl alcohol, vinyl acetate-ethylene copolymer, or a hydrolyzate of a vinyl acetate-ethylene copolymer; <1> ~ <7> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0049] <9> The glass transition point of component (A) is preferably 0°C or higher, more preferably 10°C or higher, even more preferably 20°C or higher, even more preferably 30°C or higher, and is preferably 120°C or lower, more preferably 110°C or lower, even more preferably 100°C or lower, even more preferably 90°C or lower, i.e., 0°C or higher but lower than 120°C. <1> ~ <8> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0050] <10> The weight average molecular weight of component (A) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, even more preferably 40,000 or more, and is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, even more preferably 200,000 or less. <1> ~ <9> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0051] <11> The content of component (A) in the composition for forming a self-peeling film is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, still more preferably 1.5% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, still more preferably 7% by mass or less, and still more preferably 5% by mass or less. <1> ~ <10> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0052] <12> The content of component (A) in the composition for forming a self-peeling film is preferably 1.5 to 20 mass%, more preferably 1.5 to 15 mass%, even more preferably 1.5 to 10 mass%, even more preferably 1.5 to 7 mass%, and still more preferably 1.5 to 7 mass%. <1> ~ <10> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0053] <13> The sulfonation rate of component (B) is preferably 95% or more, more preferably 98% or more, and even more preferably 99% or more. <1> ~ <12> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0054] <14> The glass transition point of component (B) is preferably 210°C or higher, more preferably 300°C or higher, even more preferably 400°C or higher, and even more preferably 440°C or higher. <1> ~ <13> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0055] <15> The weight average molecular weight of component (B) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, even more preferably 100,000 or more, and is preferably 10,000,000 or less, more preferably 5,000,000 or less, even more preferably 2,000,000 or less. <1> ~ <14> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0056] <16> The content of component (B) in the composition for forming a self-peeling film is preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 8% by mass or more, still more preferably 10% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, still more preferably 25% by mass or less. <1> ~ <15> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0057] <17> The content of component (B) in the composition for forming a self-peeling film is preferably 5 to 50 mass%, more preferably 7 to 40 mass%, even more preferably 8 to 30 mass%, still more preferably 8 to 20 mass%, and even more preferably 10 to 25 mass%. <1> ~ <15> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0058] <18> the mass ratio of component (B) to the total amount of component (A) and component (B), (B) / [(A)+(B)], is preferably 0.65 or more, more preferably 0.70 or more, even more preferably 0.75 or more, and still more preferably 0.80 or more, and is preferably 0.94 or less, more preferably 0.93 or less; <1> ~ <17> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0059] <19> the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is preferably 0.70 to 0.94, more preferably 0.75 to 0.94, even more preferably 0.75 to 0.93, and still more preferably 0.80 to 0.93; <1> ~ <17> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0060] <20> Component (C) is preferably selected from water and a volatile organic solvent, more preferably contains water, and even more preferably is mainly composed of water; <1> ~ <19> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0061] <21> The vapor pressure of component (C) at 20°C is preferably 0.01 kPa or more and 106.66 kPa or less, more preferably 0.13 kPa or more and 66.66 kPa or less, even more preferably 0.67 kPa or more and 40.00 kPa or less, and even more preferably 1.33 kPa or more and 40.00 kPa or less. <1> ~ <20> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0062] <22> The content of component (C) in the composition for forming a self-peeling film is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less. <1> ~ <21> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0063] <23> Further, it contains potassium iodide as component (D). <1> ~ <22> 2. The method or use for removing pollutants according to any one of the preceding claims.
[0064] <24> The content of component (D) in the composition for forming a self-peeling film is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 3% by mass or more, and is preferably 15% by mass or less, more preferably 12% by mass or less, even more preferably 10% by mass or less. <23> 2. A method or use for removing pollutants as described above.
[0065] <25> A composition for forming a self-peeling film, comprising the following components (A) to (C), wherein the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
[0066] <26> A composition for forming a self-peeling film, comprising the following components (A) to (C), and having a peeling degree of 20% or more and 100% or less as measured by the evaluation method described below. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents <Evaluation method> The composition was applied at 0.3 g / cm to an epoxy resin-coated substrate. 2 The adhesive area S1 of the composition that has spread wet on the substrate before drying and the area S2 of the coating film that is in contact with the substrate after drying are measured, and the calculated value (S1-S2) / S1 is the degree of peeling.
[0067] <27> Component (A) is polyvinyl alcohol, anionically modified polyvinyl alcohol, cationically modified polyvinyl alcohol, vinyl acetate-ethylene copolymer, or a hydrolyzate of a vinyl acetate-ethylene copolymer; <25> or <26> The self-peeling film forming composition according to claim 1 .
[0068] <28> The glass transition point of component (A) is preferably 0°C or higher, more preferably 10°C or higher, even more preferably 20°C or higher, even more preferably 30°C or higher, and is preferably 120°C or lower, more preferably 110°C or lower, even more preferably 100°C or lower, even more preferably 90°C or lower, i.e., 0°C or higher but lower than 120°C. <25> ~ <27> The self-peeling film forming composition according to any one of claims 1 to 7.
[0069] <29> The weight average molecular weight of component (A) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, even more preferably 40,000 or more, and is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, even more preferably 200,000 or less. <25> ~ <28> The self-peeling film forming composition according to any one of claims 1 to 7.
[0070] <30> The content of component (A) in the composition for forming a self-peeling film is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, still more preferably 1.5% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, still more preferably 7% by mass or less, and still more preferably 5% by mass or less. <25> ~ <29> The self-peeling film forming composition according to any one of claims 1 to 7.
[0071] <31> The content of component (A) in the composition for forming a self-peeling film is preferably 1.5 to 20 mass%, more preferably 1.5 to 15 mass%, even more preferably 1.5 to 10 mass%, even more preferably 1.5 to 7 mass%, and still more preferably 1.5 to 7 mass%. <25> ~ <29> The self-peeling film forming composition according to any one of claims 1 to 7.
[0072] <32> The sulfonation rate of component (B) is preferably 95% or more, more preferably 98% or more, and even more preferably 99% or more. <25> ~ <31> The self-peeling film forming composition according to any one of the above items.
[0073] <33> The glass transition point of component (B) is preferably 210°C or higher, more preferably 300°C or higher, even more preferably 400°C or higher, and even more preferably 440°C or higher. <25> ~ <32> The self-peeling film forming composition according to any one of claims 1 to 7.
[0074] <34> The weight average molecular weight of component (B) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, even more preferably 100,000 or more, and is preferably 10,000,000 or less, more preferably 5,000,000 or less, even more preferably 2,000,000 or less. <25> ~ <33> The self-peeling film forming composition according to any one of claims 1 to 7.
[0075] <35> The content of component (B) in the composition for forming a self-peeling film is preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 8% by mass or more, still more preferably 10% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, still more preferably 25% by mass or less. <25> ~ <34> The self-peeling film forming composition according to any one of claims 1 to 7.
[0076] <36> The content of component (B) in the composition for forming a self-peeling film is preferably 5 to 50 mass%, more preferably 7 to 40 mass%, even more preferably 8 to 30 mass%, still more preferably 8 to 20 mass%, and even more preferably 10 to 25 mass%. <25> ~ <35> The self-peeling film forming composition according to any one of claims 1 to 7.
[0077] <37> the mass ratio of component (B) to the total amount of component (A) and component (B), (B) / [(A)+(B)], is preferably 0.65 or more, more preferably 0.70 or more, even more preferably 0.75 or more, and still more preferably 0.80 or more, and is preferably 0.94 or less, more preferably 0.93 or less; <25> ~ <36> The self-peeling film forming composition according to any one of claims 1 to 7.
[0078] <38> the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is preferably 0.70 to 0.94, more preferably 0.75 to 0.94, even more preferably 0.75 to 0.93, and still more preferably 0.80 to 0.93; <25> ~ <36> The self-peeling film forming composition according to any one of claims 1 to 7.
[0079] <39> Component (C) is preferably selected from water and a volatile organic solvent, more preferably contains water, and even more preferably is mainly composed of water; <25> ~ <38> The self-peeling film forming composition according to any one of claims 1 to 7.
[0080] <40> The vapor pressure of component (C) at 20°C is preferably 0.01 kPa or more and 106.66 kPa or less, more preferably 0.13 kPa or more and 66.66 kPa or less, even more preferably 0.67 kPa or more and 40.00 kPa or less, and even more preferably 1.33 kPa or more and 40.00 kPa or less. <25> ~ <39> The self-peeling film forming composition according to any one of claims 1 to 7.
[0081] <41> The content of component (C) in the composition for forming a self-peeling film is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less. <25> ~ <40> The self-peeling film forming composition according to any one of claims 1 to 7.
[0082] <42> Further, it contains potassium iodide as component (D). <25> ~ <41> The self-peeling film forming composition according to any one of claims 1 to 7.
[0083] <43> The content of component (D) in the composition for forming a self-peeling film is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 3% by mass or more, and is preferably 15% by mass or less, more preferably 12% by mass or less, even more preferably 10% by mass or less. <42> The self-peeling film forming composition according to claim 1 .
[0084] <44> Further, the composition contains a surfactant, a thickener, a plasticizer or a preservative. <25> ~ <43> The self-peeling film forming composition according to any one of claims 1 to 7. EXAMPLES
[0085] Examples 1 to 6, Comparative Examples 1 to 3 The compositions shown in Table 1 were prepared, and the peeling degree (%) and film strength were evaluated according to the methods described below.
[0086] (Method for evaluating peeling degree) Each composition was applied to 10 cm of the cement-solidified substrate. 2 in the range of 0.3g / cm 2 The coating was applied and dried at 25°C and 40% RH for 24 hours to prepare a sample. The adhesion area S1 of the composition that has spread wet on the substrate before drying and the area S2 of the coating film that is in contact with the substrate after drying are measured, and the calculated value (S1-S2) / S1 is the degree of peeling.
[0087] (Membrane strength evaluation method) The composition was dried on a glass plate or a Teflon (registered trademark) sheet in an environment of 25°C and 50%RH humidity to a dry film thickness of 500 μm to obtain a dried film. The obtained film was folded 180° and then opened. When it did not break, it was rated as a, when it broke, it was rated as c, when it had creases or cracks but did not break, it was rated as b.
[0088] <Glass transition temperature> The glass transition points of the components (A) and (B) described in the examples were determined by drying each sample at room temperature for 24 hours and then further drying under reduced pressure at 80°C to obtain a dried solid, which was then subjected to DSC measurement under the following conditions. Measurement equipment: DSC7000X (Hitachi High-Tech Science Corporation) Temperature profile: 1. Raise temperature from 20℃ to the target temperature at 10℃ / min and maintain for 5 minutes 2. Cool from the target temperature to 20°C at 10°C / min and hold for 5 minutes 3. Raise the temperature from 20°C to the target temperature at 10°C / min and hold for 5 minutes. 4. Cool from the target temperature to 20°C at 10°C / min and hold for 5 minutes The target temperatures for measurements were 250°C for Kuraray Poval 22-98, 5-98, and Exeval RS-2117, 440°C for PS-100 and PS-50, and 100°C for HA-LATEX.
[0089] [Table 1]
[0090] Test Examples 1-3 The color change of the composition of Example 2 and a composition obtained by adding 2 mass % or 5 mass % potassium iodide to the composition of Example 2 and reducing the same amount of water was evaluated according to the following method. (Hue change evaluation method) As an alternative to radiation exposure testing, a UV-C exposure test was performed in the following manner. Each composition was applied to 10 cm of polyester substrate. 2 in the range of 0.1 g / cm 2 The coating was applied, and dried for 24 hours under fluorescent light and UV-C light at 25°C and 40% RH, and the change in color was visually observed. Fluorescent light irradiation was performed in a normal laboratory environment. The UV-C lamp was a compact germicidal lamp GPL27 manufactured by Sankyo Electric Co., Ltd., and was placed 15 cm away from the light source.
[0091] As a result, the composition of Example 2 showed no change in hue under either fluorescent light or UV-C irradiation. On the other hand, the compositions of Example 2 to which 2% or 5% by mass of potassium iodide was added showed no change in hue under fluorescent light irradiation, but turned brown under UV-C irradiation. The addition of potassium iodide did not affect the peeling degree or film strength.
Claims
1. 1. A method for removing contaminants from a target surface, comprising: A process of applying a self-peeling film-forming composition containing the following components (A) to (C), in which the mass ratio of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less (B) / [(A)+(B)], to a target surface having contaminants attached thereto, to form a coating film; drying the coating; removing contaminants together with the coating film by self-peeling of the coating film accompanying the drying; A method for removing contaminants comprising: (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
2. 2. The method of claim 1, wherein the step of removing the contaminants along with the coating comprises the step of recovering the peeled, dried coating.
3. 3. The method for removing contaminants according to claim 1 or 2, wherein the coating of the self-peeling composition peels off from the periphery as it dries.
4. The amount of the self-releasing composition applied to the target surface is 0.1 kg / m 2 The method for removing pollutants according to claim 1 or 2.
5. 3. The method for removing pollutants according to claim 1 or 2, wherein the drying step is carried out in an environment of -10°C or higher and 60°C or lower.
6. 3. The method for removing pollutants according to claim 1 or 2, wherein the glass transition point of component (A) is 0°C or higher and 120°C or lower.
7. 3. The method for removing pollutants according to claim 1 or 2, wherein the polymer containing vinyl alcohol as a constituent unit of component (A) is polyvinyl alcohol, anion-modified polyvinyl alcohol, cation-modified polyvinyl alcohol, vinyl acetate-ethylene copolymer, or a hydrolysate thereof.
8. 3. The method for removing pollutants according to claim 1 or 2, wherein component (B) is polystyrene sulfonic acid or a salt thereof having a weight average molecular weight of 5,000 or more and 10,000,000 or less.
9. 3. The method for removing pollutants according to claim 1 or 2, wherein component (C) comprises water.
10. Use of a composition for forming a self-peeling film, which contains the following components (A) to (C), and in which the mass ratio of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less, (B) / [(A)+(B)], for removing contaminants from a target surface by self-peeling as the coating film dries. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
11. A composition for forming a self-peeling film, comprising the following components (A) to (C), wherein the mass ratio (B) / [(A)+(B)] of component (B) to the total amount of components (A) and (B) is 0.6 or more and 0.95 or less. (A) A polymer containing vinyl alcohol as a structural unit (B) Polystyrene sulfonic acid or its salts having a sulfonation rate of 89% or more (C) Volatile Solvents
12. The self-peeling film forming composition according to claim 11, wherein the glass transition point of component (A) is 0°C or higher and 120°C or lower.
13. 13. The self-peeling film forming composition according to claim 11 or 12, wherein the component (B) is polystyrene sulfonic acid or a salt thereof having a weight average molecular weight of 5,000 or more and 10,000,000 or less.
14. The self-peeling film forming composition according to claim 11 or 12, wherein the glass transition point of component (B) is 210°C or higher.
15. The self-peeling film forming composition according to claim 11 or 12, further comprising component (D) potassium iodide.